2013
DOI: 10.37236/2639
|View full text |Cite
|
Sign up to set email alerts
|

Metric Dimension for Random Graphs

Abstract: The metric dimension of a graph G is the minimum number of vertices in a subset S of the vertex set of G such that all other vertices are uniquely determined by their distances to the vertices in S. In this paper we investigate the metric dimension of the random graph G(n, p) for a wide range of probabilities p = p(n).1991 Mathematics Subject Classification. 05C12, 05C35, 05C80.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
0
39
1
Order By: Relevance
“…for brevity, if lim n→∞ Pr(E n ) = 1. The metric dimension of G n,p was studied by Bollobás et al [1]. If we specialize their result to large p then it can be expressed as:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…for brevity, if lim n→∞ Pr(E n ) = 1. The metric dimension of G n,p was studied by Bollobás et al [1]. If we specialize their result to large p then it can be expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…Note that the upper and lower bounds in (1) are asymptotically equal if p ≥ n −o (1) . It is well-known (see, e.g., [5]) that if np 2 ≥ 2 log n + ω, then a.a.s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bound has been generalized to encompass arbitrary values of p so that, with high probability, β(G n,p ) ≤ −3 ln(n) ln(p 2 +(1−p) 2 ) as n goes to infinity and any set of nodes of this size resolves the graph with high probability [26]. Focusing closely on different regimes of p as a function of the graph size, much more precise bounds on β(G n,p ) have been established [3].…”
Section: Complexity and Approximation Algorithmsmentioning
confidence: 99%
“…In [1], Bollobás, Mitsche and Pralat computed an asymptotic for dim(G(n, p)) for a wide range of probabilities p(n) as a function of n. For instance, for constant p ∈ (0, 1), it was shown that dim(G(n, p)) = (1 + o(1)) 2 log(n) log(1/Q) ,…”
Section: Introductionmentioning
confidence: 99%